2013
DOI: 10.1080/13636820.2013.853685
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing entrepreneurial self-efficacy through vocational entrepreneurship education programmes

Abstract: The purpose of this study is to report the results of a longitudinal evaluation of a vocational entrepreneurship education programme (EEP) using entrepreneurial self-efficacy (ESE) measures. An empirical, mixed methods longitudinal and effectuation scale was used to measure ESE scores. Results indicate that participation in the programme had a positive significant effect on the ESE scores of all participants. In particular, the increase in scores for women, participants aged more than 40, and participants who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 46 publications
3
26
0
5
Order By: Relevance
“…Self-efficacy is defined as people's beliefs about their capabilities to produce designated levels of performance that exercise influence over events that affect their lives (Bandura 1994:2). Self-efficacy is one of the constructs of social cognitive theory; it is someone's belief in their own ability to successfully perform a task (Maritz & Brown, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy is defined as people's beliefs about their capabilities to produce designated levels of performance that exercise influence over events that affect their lives (Bandura 1994:2). Self-efficacy is one of the constructs of social cognitive theory; it is someone's belief in their own ability to successfully perform a task (Maritz & Brown, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy is a motivational construct that has been shown to influence the choice of individual activity, goal level, persistence and performance in various contexts [5]. [6] Demonstrates the results of selfefficacy studies that demonstrate consistent findings, as has been shown to be related to performance, facing tasks related to difficult careers, learning, and achievement and ability to adapt to new technologies. Self-efficacy is associated with the achievement of academic goals [7].…”
Section: Introductionmentioning
confidence: 88%
“…Several researchers focus on evaluating the impact of EE on individuals’ intentions to develop a business on traditional antecedents of intentions such as self-efficacy (e.g., Cox et al, 2002 ; Maritz and Brown, 2013 ; Piperopoulos and Dimov, 2015 ). General self-efficacy refers to an individual’s estimation regarding his or her general ability to act successfully ( Chen et al, 2001 ).…”
Section: The Narrative Frameworkmentioning
confidence: 99%